Thrombopoietin mutation in congenital amegakaryocytic thrombocytopenia treatable with romiplostim. Issue 1 (30th November 2017) - Pecci, Alessandro; Ragab, Iman; Bozzi, Valeria; De Rocco, Daniela; Barozzi, Serena; Giangregorio, Tania; Ali, Heba; Melazzini, Federica; Sallam, Mohamed; Alfano, Caterina; Pastore, Annalisa; Balduini, Carlo L; et al.
Abstract: Congenital amegakaryocytic thrombocytopenia (CAMT) is an inherited disorder characterized at birth by thrombocytopenia with reduced megakaryocytes, which evolves into generalized bone marrow aplasia during childhood. Although CAMT is genetically heterogeneous, mutations of MPL, the gene encoding for the receptor of thrombopoietin (THPO), are the only known disease‐causing alterations. We identified a family with three children affected with CAMT caused by a homozygous mutation (p.R119C) of the THPO gene. Functional studies showed that p.R119C affects not only ability of the cytokine to stimulate MPL but also its release, which is consistent with the relatively low serum THPO levels measured in patients. In all the three affected children, treatment with the THPO‐mimetic romiplostim induced trilineage hematological responses, remission of bleeding and infections, and transfusion independence, which were maintained after up to 6.5 years of observation. Recognizing patients with THPO mutations among those with juvenile bone marrow failure is essential to provide them with appropriate substitutive therapy and prevent the use of invasive and unnecessary treatments, such as hematopoietic stem cell transplantation or immunosuppression. Synopsis: Congenital amegakaryocytic thrombocytopenia (CAMT) is a fatal inherited juvenile bone marrow failure syndrome, unless children are treated with hematopoietic stem cell transplantation (HSCT). The only known cause of CAMT is mutations in the MPL gene. A novel THPO mutation is here described. We identified a family affected with CAMT that is caused by a novel homozygous missense mutation (p.R119C) in THPO, the gene encoding for thrombopoietin (THPO). Functional studies in vitro showed that p.R119C significantly impairs secretion of THPO, consistent with the relatively low serum THPO levels measured in patients. The mutation also affects interaction of THPO with MPL, resulting in defective signalling downstream of the receptor, which is reduced by about 50% compared with wild‐type THPO. In three affected children, administration of the THPO‐mimetic romiplostim induced sustained trilineage improvement of blood counts and remission of bleeding and infections, maintained after an up to 6.5‐year follow‐up. THPO mutations must be considered in patients presenting with the phenotype of CAMT: recognition of this disorder (disease variant) is essential to avoid unnecessary HSCT and give appropriate substitutive therapy with MPL agonists. Abstract : Congenital amegakaryocytic thrombocytopenia (CAMT) is a fatal inherited juvenile bone marrow failure syndrome, unless children are treated with hematopoietic stem cell transplantation (HSCT). The only known cause of CAMT is mutations in the MPL gene. A novel THPO mutation is here described.